International perspectives on emerging trends and integrating research-based learning across the curriculum - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2021)
In the 21st century global knowledge economy, research based universities occupy prime position, and have multiple roles to play beyond teaching, learning and supporting the academic achievements of students. Offering an international perspective, this book demonstrates how these emerging trends are being viewed across different countries with a broad range of completely diverse socio-cultural backgrounds. The authors explore the contribution of universities towards the advancement of global science and scholarship in countries like Turkey, Kosovo, Latin America and US. Delving into new information and processes across these countries, they investigate how the future of academic research is changing, evolving, and ultimately contributing towards emerging trends which are significant in shaping the academic and societal roles played by universities, and in understanding the human condition. It is by engaging in this research that the authors demonstrate to readers how culture, technology and society interact within and beyond the academic space, and are rooted in the foundation of intellectual and scientific trends.